Analisis Keterlambatan Penerbitan Certificate of Pratique (COP) Kapal Asing pada Karantina Kesehatan Banten oleh PT. Bahari Tirta Jaya Cabang Banten - Elman Syahputra Silitonga; Syarifur Ridho; Dina Rispianti (Politeknik Pelayaran Sulawesi Utara, 2025)
This study aims to identify the factors causing delays in the issuance of the Certificate of Pratique (COP) for foreign vessels and to review the standard procedures applicable at the Banten Health Quarantine through the role of PT. Bahari Tirta Jaya Banten Branch. The COP is a critical document certifying that a vessel has met health requirements and is permitted to have contact with the shore (berthing/stevedoring). The research method employed is field research through direct observation at the port and library research involving laws, regulations, and relevant port literature. The research findings indicate that delays in COP issuance are caused by several primary factors, including: (1) incomplete ship administrative documents, (2) quarantine procedures requiring additional inspections, (3) poor ship hygiene conditions, (4) limited human resources within the quarantine office, and (5) technical constraints in the quarantine information system. These delays have a significant impact on ship berthing schedules, the efficiency of loading and unloading processes, and potential financial losses for shipping companies. This study recommends the need for improved coordination between ship agents and Health Quarantine authorities, evaluation of procedural efficiency, and strengthening of information system resources to ensure smooth services within the Banten Port area.